Sustainable development as post-modern culture - Malaska, Pentti (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 1997)
Sustainable development is the post-modern idea of progress with a principia ethica emerging from the failures and achievements of the modern project of Enlightenment. The paper describes the course of human development with these terms and concepts of the modern dilemma.